Between Egypt, Mesopotamia and Scandinavia: Late Bronze Age glass beads found in Denmark. (February 2015) - Varberg, Jeanette; Gratuze, Bernard; Kaul, Flemming
Abstract: New research results from glass beads found in Denmark reveal surprising evidence for contact in the 14th–12th centuries BC between Egypt, Mesopotamia and Denmark, indicating a complex and far-reaching trade network. 290 annular glass beads ranging from dark blue to green, white and yellow, along with four polychrome beads, have been found in 14th–12th century burials from Denmark and Schleswig-Holstein in North Germany. Coming from well dated contexts, twenty-three well-preserved Danish glass beads were chosen for analysis. Graphical abstract: Highlights: We show evidence of far trade contact between Egypt, Mesopotamia and Denmark. We examine Late Bronze Age glass beads found in Danish graves. The glass found in Denmark comes from workshops in New Kingdom Egypt and Mesopotamia. Glass beads from Danish graves are the only finds of Egyptian glass outside the Mediterranean area. Based on these results we show the importance of amber and glass trade in Late Bronze Age.